2009
DOI: 10.1016/j.cell.2009.08.034
|View full text |Cite|
|
Sign up to set email alerts
|

Writing Memories with Light-Addressable Reinforcement Circuitry

Abstract: Dopaminergic neurons are thought to drive learning by signaling changes in the expectations of salient events, such as rewards or punishments. Olfactory conditioning in Drosophila requires direct dopamine action on intrinsic mushroom body neurons, the likely storage sites of olfactory memories. Neither the cellular sources of the conditioning dopamine nor its precise postsynaptic targets are known. By optically controlling genetically circumscribed subsets of dopaminergic neurons in the behaving fly, we have m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
361
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 448 publications
(384 citation statements)
references
References 47 publications
21
361
2
Order By: Relevance
“…DA) neurons were transiently activated in place of electric shocks [8,33]. These studies showed that components of the DA circuit are sufficient to communicate an aversive stimulus in association with odours in adult flies.…”
Section: Another View: Da and Suppression Effectsmentioning
confidence: 87%
“…DA) neurons were transiently activated in place of electric shocks [8,33]. These studies showed that components of the DA circuit are sufficient to communicate an aversive stimulus in association with odours in adult flies.…”
Section: Another View: Da and Suppression Effectsmentioning
confidence: 87%
“…This work demonstrates a direct role of DA in nutrient sensing and food rejection in flies; however, its role in aversive learning is well established. The activity of the PPL1 cluster of DA neurons in the adult fly brain can produce aversive memory when paired with an odor (Claridge-Chang et al, 2009;Aso et al, 2010). Distinct DA neurons in the PPL1 cluster provide motivational control over memory expression, suggesting that these neurons constitute a dopaminergic circuitry that regulates the internal motivational state of hunger and satiety (Krashes et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Memory is involved in the adaptation to long-term EAAD exposure. Moreover, dopamine plays a critical role in aversive and appetitive memories in the mushroom bodies, the learning and memory center in the Drosophila brain (Claridge-Chang et al, 2009;Krashes et al, 2009;Aso et al, 2010;Burke et al, 2012;Liu et al, 2012a). D 0 neurons project to the mushroom body as well as to the SOG (Figures S4B and S4C).…”
Section: Identification Of the Eaad-sensing Neuronsmentioning
confidence: 95%
“…Calcium imaging experiments have indicated that PPL1 neuronal processes innervating the tip of the α lobe and the lower stalk/junction show preferential responses to electric shock [94]. Furthermore, utilizing an optical method to activate genetically restricted DA neuron subtypes, PPL1 neurons have been identified as sufficient for directing aversive reinforcement to form aversive olfactory memory in behaving flies [95].…”
Section: Monoaminergic Input To Mb Neuronsmentioning
confidence: 99%
“…Abbreviations: AL, antennal lobe; LH, lateral horn; MB, mushroom body; PN, projection neuron; DPM, dorsal paired medial neuron; APL, anterior paired lateral neuron; DA, dopaminergic neurons; PPL1 DA, PPL1 cluster of dopaminergic neurons. The schematic incorporates information from references[53,60,[94][95][96]112].…”
mentioning
confidence: 99%